The Evaluation of shelf life of Arabica mixed coffee drinks using accelerated shelf life testing method. - Laras Cempaka; Ajeng Qonita Nugrafitri Akbar; Nurul Asiah (Indonesian Coffee and Cocoa Research Institute, 2019)
Arabica coffee drinks in this study were made from three parts of coffee beans are cascara, which is the skin of coffee fruit; green coffee beans; and roasted coffee beans. This beverage product is then packaged and stored in a ready to drink glass bottle. This study aim to determine the shelf life of mixed arabica coffee beverage products, using the ASLT method. Samples were stored under different temperature conditions: 4oC, 27oC and 37oC. The test consists of measuring pH, total dissolved solids (ppm), total sugar (oBrix), total color difference (ΔE) and total plate count (log CFU/ ml). The results showed that during storage occurred to change the physicochemical properties and the number of microbes in the mixed arabica coffee drinks. Each parameter has a different activation energy value. The higher the storage temperature was proven to the smaller the activation energy, which indicates a shorter shelf life. This arabica coffee drink has a shelf life of 4 days if stored at 4oC.